High Glucose Concentrations Affect Band 3 Protein in Human Erythrocytes - Rossana Morabito; Alessia Remigante; Sara Spinelli; Giulia Vitale; Vincenzo Trichilo; Saverio Loddo; Angela Marino (Antioxidants, 2020)
Hyperglycemia is considered a threat for cell homeostasis, as it is associated to oxidative stress (OS). As erythrocytes are continuously exposed to OS, this study was conceived to verify the impact of either diabetic conditions attested to by glycated hemoglobin (Hb) levels (>6.5% or higher) or treatment with high glucose (15–35 mM, for 24 h) on erythrocyte homeostasis. To this aim, anion exchange capability through the Band 3 protein (B3p) was monitored by the rate constant for SO42− uptake. Thiobarbituric acid reactive species (TBARS), membrane sulfhydryl groups mostly belonging to B3p, glutathione reduced (GSH) levels, and B3p expression levels were also evaluated. The rate constant for SO42− uptake (0.063 ± 0.001 min−1, 16 min in healthy volunteers) was accelerated in erythrocytes from diabetic volunteers (0.113 ± 0.001 min−1, 9 min) and after exposure to high glucose (0.129 ± 0.001in−1, 7 min), but only in diabetic volunteers was there an increase in TBARS levels and oxidation of membrane sulfhydryl groups, and a decrease in both GSH and B3p expression levels was observed. A combined effect due to the glycated Hb and OS may explain what was observed in diabetic erythrocytes, while in in vitro hyperglycemia, early OS could explain B3p anion exchange capability alterations as proven by the use of melatonin. Finally, measurement of B3p anion exchange capability is a suitable tool to monitor the impact of hyperglycemia on erythrocytes homeostasis, being the first line of high glucose impact before Hb glycation. Melatonin may be useful to counteract hyperglycemia-induced OS at the B3p level.